ChemInform Abstract: Flexible Routes to Thiophenes. Issue 23 (10th June 2014) - Jullien, Helene; Quiclet‐Sire, Beatrice; Tetart, Thomas; Zard, Samir Z.
Abstract Three convergent routes for the preparation of thiophenes are described.